Window gardening - Cotton, Charlotte Mabel (My University, 1896)
Introduction: “Bright gems of Earth in which perchance we see what Eden was – what Paradise may be.” Without them life would not seem so bright to us, and to the true lover of nature they are as costly gems. They are found everywhere; away out on the broad prairies where there is no one to admire them; up on top of the mountains where no one can reach them, and down in the valleys where all may have them if they wish. There are flowers found in every part of the earth; from the hot sultry climate of the torrid zone, to the cold and wintry regions of the northern zone; they are found in the rich man’s stately mansion and in the poor man’s humble dwelling. And they impart their fragrant colors to all alike. Truly are they, “Nature’s Jewels.”
Citation: Cotton, Charlotte Mabel. Window gardening. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Paradise; Earth; Natures jewels; Theses; Manuscripts (documents)